Inhibition of p‐Nitrothiophenol Catalytic Hydrogenation on Ag‐Containing AgAu/Pd/TiO2 Plasmonic Catalysts Probed in situ by SERS. Issue 5 (27th January 2022) - Lopes, Douglas S.; Vono, Lucas L. R.; Miranda, Ester V.; Ando, Rômulo A.; Corio, Paola
Abstract: Compositional variations of surface‐enhanced Raman scattering (SERS)‐active catalysts play an essential role and can drastically affect the reaction pathway, rate, and product selectivity. Here, the Pd‐catalyzed p ‐nitrothiophenol (PNTP) to p ‐aminothiophenol (PATP) hydrogenation and the surface plasmon resonance (SPR) mediated p ‐aminothiophenol (PATP) to p, p ‐dimercaptoazobenzene (DMAB) oxidation catalytic activities over TiO2 ‐supported AgAu/Pd NPs (AgAu/Pd/TiO2 ) are investigated as a function of the Ag to Au ratio using in situ SERS. The results showed that as the PNTP hydrogenation rates grew exponentially with decreased Ag mole fraction, the yield of the PATP to DMAB conversion rapidly diminishes in the opposite trend. The observed variations in catalytic performance can be explained by the formation of surface Ag oxides in Ag‐containing substrates, leading to the inhibition of PNTP catalytic hydrogenation on Ag/Pd/TiO2 while favoring the PATP to DMAB oxidation. This work provides a concrete example of how oxidized Ag can significantly affect the catalytic activity of bifunctional substrates and can guide the rational design of SERS‐active catalysts. Abstract : In situ monitoring : The formation of surface oxidized Ag in Ag‐containing AgAu/Pd/TiO2 SERS‐active catalysts leads to the inhibition of p ‐nitrothiophenol (PNTP) catalytic hydrogenation while favoring the p ‐aminothiophenol (PATP) to p, p ‐dimercaptoazobenzene (DMAB) oxidation. Catalytic activity experiments were monitored using in situ SERS.